Experience of the monitoring process in modular disciplines with active methodology (Research, Society and Development, 2023)
Monitoring dates back to Classical Antiquity, being linked to the function of helping the master, simplifying classes and disciplinary control of students. Only in the Modern Age is tutoring associated with mutual teaching through the Lancaster Method – which favors the most advanced student to help others, under the guidance of a teacher. In this sense, the objective of this work is to demonstrate the importance of the monitoring process in the medical course through the experience report. This work is a descriptive study, type of experience report, carried out at Faculdade Pitágoras Medicina de Codó, from October to November 2022. During the monitoring period, it was possible to observe the benefits of student participation in classes in the way that the content was better assimilated. In this activity, it was observed that the monitoring facilitated the teaching-learning process of the medical students in the presented module, provided the monitor with a teaching experience and offered the students a better quality training in the module described. Thus, it is concluded that the active learning of the monitoring program is conducive to collaborative learning environments, shaping the student's knowledge, enhancing the learning process in colleges, developing pedagogical skills and deepening the knowledge of the monitors.